Littérature, représentations de soi et mobilité sociale dans le québec du XIXe siècle - Hubert, Ollivier (Recherches sociographiques, 2003)
Is it possible to write a history of the “popular” ways of telling one’s story in periods prior to the democratization of writing ? Due to a scarcity of source material, this is no easy task. However, there are sophisticated self-representations available to the historian, produced by certain literate individuals from modest backgrounds. An analysis of part of the literary output of a representative of this category, Antoine Gérin-Lajoie, may be used to follow the process of shifting from an autobiographical narration to a sociological reflection. This reveals that the very fact of experiencing the problems involved in acquiring a scholarly culture, and in social mobility, provides part of the foundation for these writings on oneself and on the world.